Sosialisasi Penggunaan Pupuk bioorganik-fosfat Pada Tanaman Cabai Merah (Capsicum annum L) - Lolita Endang Susilowati; Zaenal Arifin (Universitas Mataram, 2020)
Bioorganic-phosphate fertilizer is an organic fertilizer enriched with phosphate solubilizing rhizobacteria (PSR). The addition of PSR to organic fertilizers is intended to improve the quality of organic fertilizer. The purpose of this community service activity is to socialize the use of bioorganic-phosphate fertilizers on red chili plants for reducing the use of inorganic fertilizers. This service activity used a participatory approach. As a target farmer partner is the